Imagining the Nation : History, Modernity, and Revolution in Latvia - Eglitis, Daina Stukuls (Book collections on Project MUSE., 2002)
Ultimately, the changes in Latvia and other East European countries are closely tied to a vital reimagining of the past, as the logic of progress long associated with "revolution" is amalgamated with nostalgia for what is gone. The radiant utopias of revolution give way to widely shared aspirations for a return to the normal in politics, place names, private property, and even gender relations." "Eglitis draws upon published and unpublished documents, campaign posters, maps, and monuments, as well as interviews with Latvians from all walks of life."--Jacket.